THE EXPONENT SET OF COMPLETE ASYMMETRIC 2-DIGRAPHS - Saib Suwilo (Proceedings of ICMSA, 2005)
A 2-digraph is a digraph whose each ofits arcs is colored by either redor blue. The exponent ofa 2-digraphD is the smallest positive integerh + k over all possible nonnegative integers h and k such that for eachpair of vertices u and v in D there is a walk from u to v consisting of hred arcs and k blue arcs. In this paper, we show that for n 5 theexponent set of complete asymmetic 2-digraphs on n vertices is Eo :2,3,4.Keywords: 2-digraphs, primitive, exponent.